Emergy evaluation and economic analysis of compound fertilizer production: A case study from China. (1st July 2020) - Chen, Yuhong; Zhang, Xiaohong; Yang, Xiangdong; Lv, Yanfeng; Wu, Jun; Lin, Lili; Zhang, Yanzong; Wang, Guiyin; Xiao, Yinlong; Zhu, Xuemei; Yu, Xiaoyu; Peng, Hong
Abstract: The compound fertilizer market has an increasing share in the Chinese chemical fertilizer consumption. However, this industry is challenged by the increasing use of nonrenewable resources and pollution emissions. Therefore, promoting the sustainability of this industry is urgent. This study proposes a combination of improved emergy analysis methods and an economic evaluation to comprehensively assess the compound fertilizer production. The proposed methods quantify the adverse effects of pollution emissions and the effect of one subsystem on the integrated system. A case study was conducted on a compound fertilizer enterprise in the Jiangxi Province of China and the following conclusions were drawn: 97.82% of the emergy input to the system comes from the nonrenewable resources (especially urea and ammonium dihydrogen phosphate); the ecological services and emergy loss derived from pollution discharge, mainly from HCl gas and dust emissions, reach 7.68E+17 sej/yr and 5.76E+17 sej/yr, respectively, which reduce the environmental sustainability level of the integrated system by 0.03%; the improved emergy sustainability index values of the integrated system and its subsystems range between 0.0203–0.0228, which indicates their long-term unsustainability; the nitro-water-soluble fertilizer subsystem has the largest adverse effect on the sustainability of the enterprise (0.24); the environmental contribution is far underestimated by 78–98% in the prices of the four kinds of fertilizers investigated in this study; the sulfur-based fertilizer subsystem has the highest economic benefit (net economic benefit ratio = 0.31) but the least environmental sustainability (improved emergy sustainability index = 0.0203) among the four subsystems. Finally, this study proposes promoting green procurement of main raw materials, optimizing the existing processes, improving the environmental performance of the sulfur-based fertilizer subsystem, and increasing the prices of compound fertilizers. Highlights: Performance evaluation of a compound fertilizer system was implemented. Air emissions slightly weaken its environmental sustainability level. High share of purchased non-renewable resources causes its unsustainability. Nitro-water-soluble fertilizer subsystem maximally affects its sustainability. Sulfur-based fertilizer subsystem has the worst environmental performance.